Diversión y Juegos : a Tiempo para el Parque de Atracciones - Medición Del Tiempo (Fun and Games - Clockwork Carnival: Measuring Time). - Conklin, Wendy (Mathematics in the Real World Ser., 2018)
Spend a fun day at the carnival and learn how to measure time with this Spanish math reader! This fiction text integrates math and literacy skills, and uses practical, real-world examples to help students explore math in a meaningful way.